Diagnostic and Prognostic Value of MicroRNAs in Metastasis and Recurrence of Head and Neck Squamous Cell Carcinoma: A Systematic Review and Meta-Analysis - Qiu, Ke; Song, Yao; Rao, Yufang; Liu, Qiurui; Cheng, Danni; Pang, Wendu; Ren, Jianjun; Zhao, Yu (Frontiers in Oncology, 2021)
MicroRNAs have been proven to make remarkable differences in the clinical behaviors of head and neck squamous cell carcinoma (HNSCC). This study aims to systematically analyze whether differential expression levels of microRNAs are related to recurrence or metastasis in patients with HNSCC. A comprehensive search of the PubMed, EMBASE, and CENTRAL was conducted up to July 24th, 2021. Data were collected and combined from studies reporting recurrence-free survival (RFS) of HNSCC patients with high microRNA expression compared to those with low expression. Besides, studies providing necessary data for evaluating the diagnostic value of microRNAs for detecting recurrence and metastasis based on their expression levels were also included and combined. The pooled hazard ratio (HR) value for the outcomes of RFS in 1,093 HNSCC samples from 10 studies was 2.51 (95%CI: 2.13–2.96). A sensitivity of 0.79 (95% CI: 0.72–0.85) and specificity of 0.77 (95%CI: 0.68–0.83) were observed in three studies, of which 93 patients with recurrence and 82 nonrecurrence controls were included, and the area under the curve (AUC) was 0.85 (95% CI: 0.81–0.88). Additionally, high diagnostic accuracy of microRNAs in detecting lymph node metastasis (LNM) was also reported. In conclusion, two panels of microRNAs showed the potential to predict recurrence or diagnose recurrence in HNSCC patients, respectively, which could facilitate prognosis prediction and diagnosis of clinical behaviors in HNSCC patients. Systematic Review Registration PROSPERO (https://www.crd.york.ac.uk/prospero), identifier CRD42020161117.